2020
DOI: 10.1016/j.apsusc.2020.147516
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun antibacterial poly(vinyl alcohol)/Ag nanoparticles membrane grafted with 3,3′,4,4′-benzophenone tetracarboxylic acid for efficient air filtration

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…where ρ 0 = 1.27 g/cm 3 , representing the standard density of PLA. Each sample was cut into 5 × 5 cm size, whose thickness and weight were measured with a digital thickness meter (YG141A, Wenzhou Jigao Testing Instrument Co., Ltd., Wenzhou, China) and a balance (FA1004N, Shanghai Jinghai Instrument Co., Ltd., Shanghai, China) to calculate the corresponding density (ρ).…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρ 0 = 1.27 g/cm 3 , representing the standard density of PLA. Each sample was cut into 5 × 5 cm size, whose thickness and weight were measured with a digital thickness meter (YG141A, Wenzhou Jigao Testing Instrument Co., Ltd., Wenzhou, China) and a balance (FA1004N, Shanghai Jinghai Instrument Co., Ltd., Shanghai, China) to calculate the corresponding density (ρ).…”
Section: Characterizationmentioning
confidence: 99%
“…Currently, the COVID-19 pandemic and the prevalence of other infectious diseases have brought a heavy impact on humans, not only in terms of human health but also in affecting national stability and global economic development [1]. Nowadays, the number of infection and death cases is still rising, causing incessant attention all over the world [2,3]. Studies have shown that several ways of transmission for SARS-CoV-2 include droplet transmission, body fluid transmission, aerosol transmission, and contact with contaminated surfaces [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ag NPs have been shown to have antibacterial, antifungal and antiviral properties [54]. In addition, Ag NPs possess anti-inflammatory properties during wound healing, so they have been widely used in the biomedical field, particularly in drug delivery, medical mask coatings, wound treatment dressings, bone implants and prostheses [43,55].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the resistance changes in the MOF-PAN hybrid fiber could sense the fast and slow breathing indicating the condition of the patient [ 73 ] Cu- 1,3,5-benzenetricarboxylic acid (BTC) MOF-based chitosan (CNF)/poly (vinyl alcohol) (PVA) electrospun nanofiber for selective CO 2 capture CNFs/BTC/Cu-3 which showed wider pore range of 0.7 to 1.1 nm. The CNF/Cu/BTC-3 also showed preferential adsorption of CO 2 to be 14 times more than N 2 at 298 K and 100 kPa [ 74 ] Antimicrobial fibers Silver nanoparticles (AgNPs) containing PVA nanofiber membranes were electrospun and grafted with 3,3′,4,4′-benzophenone tetracarboxylic acid (BPTA) which generate reactive oxygen species (OH and H 2 O 2 ) to impart antibacterial properties Tight-fitting masks with small fans performed better than masks without fans [ 75 ] AgNP containing PVDF nanofiber were electrospun for multifunctional applications by incorporating alumina Al 2 O 3 nanoparticles Membranes reduced particulates (> 99%) as well as a detoxifying model nerve agent (> 36%). The detoxifying and filtration properties improved with increasing Al 2 O 3 and were highest at 8% Al 2 O 3 [ 76 ] Electrospun chitosan/poly (vinyl alcohol) nanofiber membrane surface modified with SiO 2 and Ag nanoparticles Hydrophilic and antibacterial properties shown by membranes with addition of SiO 2 and Ag nanoparticles respectively.…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%
“…S. Li et al electrospun PVA nanofiber membranes containing Ag nanoparticles (AgNPs) and grafted with 3,3′,4,4′-benzophenone tetracarboxylic acid (BPTA) which generate reactive oxygen species (OH and H 2 O 2 ) to impart antibacterial properties that was tested for reuse for about 7 times. The membranes showed good mechanical and filtration properties (> 98%, for 300–500 nm NaCl particles) [ 75 ]. A. Vanagamudi et al fabricated antibacterial AgNP-incorporated PVDF nanofibers capable of reducing particulates (> 99%) as well as a detoxifying model nerve agent (> 36%).…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%